KEEFEKTIFAN KONSELING KELOMPOK DENGAN PENDEKATAN SOLUTION FOCUSED BRIEF COUNSELING UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA TANPA PERAN AYAH DI SMA NEGERI 9 PONTIANAK - Ramadhani, Navikha; Muhammad, Asrori; Halida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effectiveness of group counseling using the Solution Focused Brief Counseling (SFBC) approach in improving the self-confidence of students without a father’s role at SMA Negeri 9 Pontianak. The research method used is an experimental method with a non-equivalent control group design, which compares the experimental group and the control group that were not randomly selected. Both groups were given a pre-test and post-test to determine the differences in self-confidence levels before and after the treatment. The research sample consisted of 10 students who had low self-confidence and experienced the absence of a father’s role, divided into an experimental group and a control group using purposive sampling technique. Based on the calculation results, the average pre-test score of the experimental group was 113.40 and the average post-test score was 135.80, indicating an increase in self-confidence after the treatment was given. Furthermore, the calculated t-value using the Paired Sample T-Test showed a significance value less than 0.05, which means that there is a significant difference in students’ self-confidence levels before and after being given group counseling with the SFBC approach. The results of the comparison test with the control group also showed that the increase in self-confidence in the experimental group was higher than that in the control group. Thus, it can be concluded that group counseling using the Solution Focused Brief Counseling approach is effective in improving the self-confidence of students without a father’s role at SMA Negeri 9 Pontianak.